2021
DOI: 10.1108/arch-09-2020-0204
|View full text |Cite
|
Sign up to set email alerts
|

Post-occupancy evaluation of outdoor spaces on the campus of the Federal University of Juiz de Fora, Brazil

Abstract: PurposeUsing the campus of a Brazilian university as case study, this research aims to identify which aspects of the outdoor spaces are the most significant in attracting people.Design/methodology/approachThis research relies on the application of different post-occupancy evaluation (POE) methods, including user tracking, behavioural mapping and questionnaires, on one plateau of the campus.FindingsThree group of aspects (socialization, proximity and infrastructure) were identified as key elements in explaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…When determining the respondents, the study identified multiple subareas at the Site (see Figure 1), including the Square (1), small squares (2), the large lawn (3), the entrance area to ferry port (4) and the sea promenade with a lawn (5). Determination of subareas was according to their design of physical/natural characteristics, as an alternative method to that with user tracking (see Tourinho et al, 2021). A 10-min observation at each subarea helped to identify people spending this time there by sitting, standing or strolling.…”
Section: Study Site and Methodologymentioning
confidence: 99%
“…When determining the respondents, the study identified multiple subareas at the Site (see Figure 1), including the Square (1), small squares (2), the large lawn (3), the entrance area to ferry port (4) and the sea promenade with a lawn (5). Determination of subareas was according to their design of physical/natural characteristics, as an alternative method to that with user tracking (see Tourinho et al, 2021). A 10-min observation at each subarea helped to identify people spending this time there by sitting, standing or strolling.…”
Section: Study Site and Methodologymentioning
confidence: 99%
“…Basically, the campus will offer academic life for its residents, which includes correlation between lecturers and students in the knowledge transfer process. Life has an important role in determining the campus's supporting capacity for the formation of social, cultural and personal relationships [10]. Furthermore, to determine the right conditions for campus design, academic facilities and services are needed which can immediately increase the sense of ownership and learning performance [10,11].…”
Section: Campus Communal Spacesmentioning
confidence: 99%
“…Campus planning must consider the existence of various spaces into an efficient unified whole [12]. In this understanding, the existence of communal space has the most important contribution in improving the quality of life and health of academics, especially students [10,[12][13][14][15].…”
Section: Campus Communal Spacesmentioning
confidence: 99%
“…On the other hand, Tourinho et al (2021) evaluated the outdoor spaces on the campus of the Federal University of Juiz de Fora, Brazil, considering the following attributes: Proximity and accessibility, Socialization and appearance, and Existence of infrastructure. Accessible space is a visible place that is connected with its surroundings visually and can be reached physically (Carmona et al, 2012).…”
Section: Review Of Literaturementioning
confidence: 99%